Andragogy and self-directed learning pillars of adult learning theory - Ong, Iluminada (2008)
The central question of how adults learn has occupied the attention of scholars and practitioners since the founding of adult education as professional field of practice in the 1920s. Some eighty years later, we have no single answer, no one theory or model of adult learning that explains all that we know about adult learner, the various contexts where learning takes place, and the process of learning itself. What we do have is a mosaic of theories, models, set of principles, and explanations that, combined, composed the knowledge base of adult learning.The purpose of this paper is to revisit two of the foundational theories of adult learning with an eye to assessing their "staying power" as important components of our present-day understanding of adult learning.
Keywords: Adult education; Knowledge and learning; Adult learning; Andragogical learning